Causes of antepartum stillbirth in women of advanced maternal age. (February 2016) - Walker, Kate F.; Bradshaw, Lucy; Bugg, George J.; Thornton, Jim G.
Abstract: Objectives: To breakdown the causes of antepartum stillbirth by maternal age. Study design: Observational study. Setting: UK. Sample: Anonymised national data on 2850 cases of antepartum stillbirth in 2009. Statistical analysis: The association between cause of stillbirth and maternal age was examined using an adjusted multinomial logistic regression model. Risk ratios were calculated relative to stillbirth due to haemorrhage. Main outcome measures: Antepartum stillbirths classified by the Centre for Maternal and Child Enquiries (CMACE) classification. Results: Stillbirths in women aged 35 years and over are more likely to be due to major congenital anomalies (relative risk ratio (RRR) 2.0, 95% CI 1.3–3.0), mechanical causes (RRR 1.6, 95% CI 1.0–2.6), maternal disorders (RRR 2.1, 95% CI 1.2–3.6) or associated obstetric factors (RRR 2.1, 95% CI 1.1–3.9) than women less than 35. Women aged 35 years and over have a statistically significant increased risk of stillbirth due to major congenital anomalies (OR relative to live birth 1.6, 95% CI 1.3–1.9) and maternal disorders (OR 1.7, 95% CI 1.2–2.4) than younger women. Women aged 35 years and over were 30% more likely to experience a term stillbirth than women <35 years (OR 1.3, 95% CI 1.1–1.5). Stillbirth due to congenital anomaly was statistically significantly more likely in women ≥35 years. Conclusions: Advanced maternal age is a significant risk factor for antepartum stillbirth particularly at term. Attention should be given to stillbirth due to mechanical causes, maternal disorders and associated obstetric factors in such women.